Pelatihan Dan Bimbingan Teknis Pembuatan Peta Tanah Di Sekolah Menengah Atas Di Kota Kendari - Mey, Djafar; Karim, Jufri; Rustam, La Ode; Fitriani, Fitriani (Vokasi Universitas Halu Oleo, 2020)
Knowledge about the land and the skills in making land maps provided is one of the efforts made to create appropriate resources. Efforts to increase knowledge and skills that can be done are introduction of soil descriptions and profiles along with training in making land maps. The purpose of this training and technical guidance activity is to provide students with an understanding of the soil at the high school level, knowing about soil resources in detail to students, knowing the procedures for making a land map using Geographic Information Systems (GIS) and knowing how to conduct soil investigations in the field. The problem solving framework of this activity is carried out in several stages, namely preparation, preparation of training materials, presentation of material by resource persons, discussions and questions and answers, practice of making land maps, and practice of making soil profiles by dividing student groups, evaluating the results of activities and preparing reports. This training was held in SMA Neg. 4 Kendari and SMA Neg. 6 Kendari. The result of this training and technical guidance is that the trainees have added knowledge and skills in making land descriptions and profiles, as well as making land maps using the geogarfi information system application.Â Keywords:. Training Students, Land, Geographic Information Systems